The acquisition of the morphosyntactic properties of Spanish by bilingual children in advanced stages - Guijarro-Fuentes, Pedrp; Clibbens, John (Sociolinguistic Studies, 2004)
In this study we examine the development of morphosyntactical knowledge by Spanish-English and English-Spanish simultaneous bilinguals. In particular, we investigate the acquisition of verbal aspect and its semantic entailments of the Spanish preterite andimperfect tenses from a generative point of view (de Miguel, 1992; Smith, 1997). As a departure point, we would not expect to find great differences between the bilingual and monolingual grammars if both grammars evolve in a similar way; if that is not the case, and given that both languages, English and Spanish, exhibit clear differences in relation to the categories tense and aspect (Smith, 1997), we would claim that the differences could be accounted for due to the fact that one of the languages is the dominant one and due to the transference of properties from one language to another. Overall the results show that subjects do not confuse preterite and imperfect forms in production; however, the bilingual participants have problems with the aspectual feature and its semantic entailment. In the light of these results we claim that the acquisition of these two aspects of functional categories is dissociated as has been observed in L2 grammars (Lardiere, 1998a, 1998b).